2016
DOI: 10.1080/19336934.2016.1193655
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of sex-peptide in Drosophila

Abstract: The Drosophila sex-peptide (SP) has been identified as a seminal fluid component that induces postmating responses (PMRs) in the inseminated females, such as inhibition of remating and stimulation of egg-laying. SP has been thought to play a central role in sexual conflict and sexually antagonistic co-evolution. Most of the sequenced Drosophila genomes contain SP orthologs, but their functions have been poorly characterized. Recently, we have investigated cross-species activity of D. melanogaster SP by means o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 17 publications
1
29
0
Order By: Relevance
“…Ovulin orthologs are difficult to find outside the melanogaster group (Mueller et al 2005), and it is not yet known if those potential orthologs – some different enough not to cross-react with anti- melanogaster -ovulin - are functional. SP orthologs are found throughout Drosophila , though distant species’ are very different in sequence and are not functional in D. melanogaster (Tsuda et al 2015; Tsuda and Aigaki 2016). Thus, both ovulin and SP appear to be novel genes, that have evolved rapidly.…”
Section: Evolutionary Considerations Regarding Pheromonesmentioning
confidence: 99%
“…Ovulin orthologs are difficult to find outside the melanogaster group (Mueller et al 2005), and it is not yet known if those potential orthologs – some different enough not to cross-react with anti- melanogaster -ovulin - are functional. SP orthologs are found throughout Drosophila , though distant species’ are very different in sequence and are not functional in D. melanogaster (Tsuda et al 2015; Tsuda and Aigaki 2016). Thus, both ovulin and SP appear to be novel genes, that have evolved rapidly.…”
Section: Evolutionary Considerations Regarding Pheromonesmentioning
confidence: 99%
“…For example, the male seminal protein Ovulin stimulates the release of oocytes by the ovary (Heifetz et al 2005). The majority of the effects of mating on female egg production and decreased receptivity to re-mating have been attributed to the male seminal protein called Sex Peptide (SP) (Chen et al 1988; Feng et al 2014; Liu and Kubli 2003; Tsuda and Aigaki 2016). SP produces the majority of its effects by binding to a specific G-protein coupled receptor called Sex Peptide Receptor (SPR) (Yapici et al 2008), however some effects of SP may be independent of SPR (Haussmann et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Seminal proteins delivered by the male often show evidence of rapid evolution under positive selection (e.g., Haerty et al 2007). The sex peptide is found in many, but not all Drosophila species (D. mojavensis and D. grimshawi appear to lack it) and not outside of Drosophilidae (Tsuda et al 2015;Tsuda and Aigaki 2016). Its receptor, SPR, is found in most insects (Yapici et al 2008), likely because of this protein's ancestral role as a receptor for myoinhibitory peptides (Kim et al 2010;Poels et al 2010).…”
Section: Postmating Behavioral Changes In Drosophila Females: Competimentioning
confidence: 99%
“…Tsuda et al (2015) showed that D. melanogaster sex peptide can induce postmating responses and binds to the oviduct in all melanogaster-group species tested, but did not induce postmating responses in females of the obscura or willistoni groups, or D. virilis, and injection of conspecific sex peptides did not either. This suggested to Tsuda and Aigaki (2016) that the induction of postmating responses via sex peptide/SPR interaction has uniquely evolved in the melanogaster group (Tsuda and Aigaki 2016). The function of the sex peptide in the other Drosophila species remains unknown.…”
Section: Postmating Behavioral Changes In Drosophila Females: Competimentioning
confidence: 99%